GAME-THEORETIC APPROACH TO MODELING AND FORMALIZATION RELATIONS BETWEEN THE SHIP-OWNER AND MANAGER COMPANY (Transport systems and technologies, 2018)
Currently the practice of transmission of the property rights for vessel to specialized manager companies is widespread in sphere of maritime business and marine legal system. The most common formality of ship management contract is «SHIPMAN 98». Some of the wordings in this formality indicate the presence of unverifiable variables, that allows to attribute the relevant contract to incomplete contracts. This, in turn, leads to a typical problem for the theory of contracts «principal-agent» associated with asymmetric information. In connection with this research is aimed at ensuring a resistant and effectiveinteraction between the ship-owner and manager of the vessel. The paper reveals the causes and the main point of conflict between the parties of ship management contract – the ship-owner and manager of the vessel. Being based on the theoretical tools of game theory, methodical provisions to ensure the decision-making processes for the implementation of ship management contract. For this purpose, the model of conflict relations between ship-owner and manager of the vessel is formalized and classified, the typical strategies of the players are described. As the same time, the possible solutions of this game is presented, they are to achieve a sustainable and at the same time effective interaction of players, which in most cases is achieved through theircooperation. The game solution for typical ship-owner and manager, operating in the market, as well as some of their representatives, facilitates the identification of the existing relations and the implementation of strategies, ensuring their resistance and efficiency.
Keywords: ship-owner, manager of the vessel, ship management contract, conflict, game, Nash equilibrium, Pareto-optimality, resistance